The role of order and disorder in thermal and material sciences part 2: Scientific world and new insights - Šesták Jaroslav (Journal of Mining and Metallurgy. Section B: Metallurgy)
The notion of heat is thoroughly analyzed and its historical links are search particularly with relation to both the Greek philosophy (Mile in print sians Pythagoreans, atomists, etc) and the in the present day thermal physics. Fluctuation, spontaneity and chaos is discussed. Thermodynamics is reviewed in the relation to both the traditional development and the modern description of disequilibria (open systems). Effect of dissipation is shown often to provide new, self-organized structures. Exploitation of fire and its conscious use as a manufacturing power are analyzed in terms of generalized engines to act in the sense of as the information transducers. The part 2 reveals the impact of mathematics as explained on some simple cases showing development of basic ideas (vibration, topology, bifurcations etc). Earth thermal environment is discussed in relation to the existence of life (antropy principles). Alternative theory of reaction-diffusion model of the space-time is put in contrast with big bang hypothesis and related to the herewith-discussed specialty of self-catalyzed chemical reactions. The text gives a consistent view to various historical and modern concepts that emerged during the gradual understanding of order and disorder.